Acute toxicity of CCl4 but not of paracetamol induces a transcriptomic signature of fibrosis in precision-cut liver slices. Issue 5 (August 2015) - Vatakuti, Suresh; Schoonen, Willem G.E.J.; Elferink, Marieke L.G.; Groothuis, Geny M.M.; Olinga, Peter
Highlights PCLS is validated as a model to identify early gene expression changes related to fibrosis. Early fibrosis related genes are regulated in CCl4, but not in APAP treated PCLS. Predicted upstream regulators in PCLS due to CCl4 treatment are related to fibrosis.